Sigi Schmid's defensive soccer tactics - Johns, Chris; Human Kinetics (Firm) (Illinois : Human Kinetics, 2007)
Through live action demonstrations, small-sided games and team drills, Schmid covers defensive tactics such as zone defenses, pressure tactics, positional play, strategies to neutralize free kicks and corner, and more
Title from title screen
Keywords: Soccer -- Defense; Soccer -- Coaching; Soccer -- Training